2015
DOI: 10.1007/s11011-015-9683-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered long- and short-range functional connectivity in the patients with end-stage renal disease: a resting-state functional MRI study

Abstract: To investigate alterations of functional connectivity density (FCD) in patients with end-stage renal disease (ESRD) by using resting-state functional magnetic resonance imaging (rs-fMRI). Medical research ethics committee approval from Jinling hospital and written informed consent from each subject were obtained. Forty six patients with ESRD, consisting of 21 patients minimal nephrotic encephalopathy (MNE) and 25 non-nephro-encephalopathy (non-NE), as well as 23 healthy controls underwent rs-fMRI. Neuropsychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Therefore, the findings should be interpreted with caution and further study is needed to collect data from patients with chronic kidney disease (stage 4–5) without hemodialysis to be able to explore whether and how hemodialysis itself can affect the intrinsic functional connectivity. Fifth, previous revious studies indicated that abnormal long- and short-range functional connectivity density in physical disease [58,59], in the future study, we are planning to investigate the alternation of brain structural and functional hub in ESRD patients by recruiting a large sample. Lastly, due to the cross-sectional design of our study, we cannot address how the vulnerability of the patients progresses to symptom burden and if there is any possible link between the vulnerability and their risk of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings should be interpreted with caution and further study is needed to collect data from patients with chronic kidney disease (stage 4–5) without hemodialysis to be able to explore whether and how hemodialysis itself can affect the intrinsic functional connectivity. Fifth, previous revious studies indicated that abnormal long- and short-range functional connectivity density in physical disease [58,59], in the future study, we are planning to investigate the alternation of brain structural and functional hub in ESRD patients by recruiting a large sample. Lastly, due to the cross-sectional design of our study, we cannot address how the vulnerability of the patients progresses to symptom burden and if there is any possible link between the vulnerability and their risk of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI showed reduced regional homogeneity in bilateral frontal, parietal and temporal regions of the brain in patients with end-stage kidney disease, which correlated with cognitive function tests. These changes were more prominent in haemodialysis patients compared to non-dialysed end-stage kidney disease patients and correlated with CI, pre-dialysis serum creatinine and duration of haemodialysis [45-46]. Another functional MRI study of the whole brain in haemodialysis patients showed bilateral activation of hippocampus suggesting activation of memory-relevant brain areas during dialysis [47].…”
Section: Discussionmentioning
confidence: 99%
“…The cingulate gyrus is a key brain structure that regulates emotional information, learning, and memory (4). Using functional magnetic resonance imaging (fMRI), a few studies have revealed that the abnormal function of the cingulate gyrus may play a significant role in cognitive dysfunction in ESRD patients (5,6). The amplitude of low-frequency fluctuations (ALFF) in fMRI reflects the energy of signal fluctuations in the low-frequency range (0.01-0.1 Hz) at the voxel level in blood oxygen level-dependent functional magnetic resonance imaging (BOLD-fMRI) (7).…”
Section: Introductionmentioning
confidence: 99%